Adherence to a strict medication protocol can reduce length of stay in hospitalized patients with Parkinson's Disease. (2020) - Azmi, Hooman; Cocoziello, Lisa; Nyirenda, Themba; Douglas, Claudia; Jacob, Blessy; Thomas, Jewell; Cricco, Donna; Finnerty, Giuseppina; Sommer, Kirsten; Rocco, Anthony; Thomas, Randy; Roth, Patrick; et al.
Abstract: Background: Patients with Parkinson's Disease (PD) are at higher risk of complications when admitted to the hospital. Delays in PD medications and use of contraindicated medications contribute to the increased risk and prolong their lengths of stay (LOS). Using a hospital-wide PD protocol, we aimed to ensure PD medications were placed with "custom" timing to resemble the home schedules, and also to avoid ordering or administering contraindicated medications. Material and methods: 569 patients admitted in 2017 and 2018, were reviewed retrospectively. Mean age was 76.5 (SD 10.6), 332 were males and 237 were females. Charts were reviewed to assess if A) PD medications were ordered with custom timing, B) if not, were the orders changed to custom timed C) if contraindicated medications were ordered, and D) if they were administered. We also assessed the actual/expected length of stay during this time period. Chi Square and post hoc analyses were done to compare time points. Poisson regression analysis was done to assess relative improvement of variables. Results: There was a 2.7 fold increase in orders placed with custom timing in 2018 compared to 2017 (RR = 2.651, 95%CI: 1.860–3.780, p < 0.0001), and a 3.2 fold increase in correction of non-custom orders in the same time period (RR = 3.246, 95%CI: 1.875–1.619, p < 0.0001). We also observed a decrease in the actual/expected LOS ratio from 1.54  to 1.32  (p < 0.05). Conclusion: By utilizing an established platform for quality improvement, we were able to improve adherence to the home medication regimen timing in admitted PD patients. Our findings also suggests that adherence to a strict medication regimen protocol may decrease LOS for this patient population. Highlights: Adherence to PD medication timing schedule is important for PD patients. When PD patients are admitted, their medications schedules can be overlooked. These errors can increase risks and length of stay (LOS) for this population. We designed a hospital-wide protocol to encourage attention to PD medications. In the period studied, we saw increased adherence to this protocol and improved LOS.